DIALEKTIKA PENCERAHAN BUDDHISME - I Komang Suastika Arimbawa (Sanjiwani: Jurnal Filsafat, 2022)
Buddhism is one of the heterodox schools of Indian philosophy, taught by Siddārtha around the VI century BC. His teachings aim to lead his followers to nirvana, by building universal values ​​that are not compartmentalized, so that they are free from the varna system. However, after the influence of Tantra in the VII century AD, Buddhist philosophy turned to Buddhism. The problem to be analyzed in this article is “what is the dialectic of enlightenment Buddhism?” The theoretical concept used in this article is hermeneutics. This article uses qualitative research methods. The results of the analysis in this article are that the teachings of Buddhist philosophy are universal, outside of certain religions and castes. Meanwhile, Buddhism's teachings are only embraced by its followers (limited in nature). However, what connects the two is the teaching of ethics. Where the goal is to free mankind from suffering. Thus, the relationship between the three forms a dialectic.